Consumers’ awareness, perception and attitude towards restaurant green practices and its influence on behaviour intentions / Aikal Liyani Mohd Rasdi - Mohd Rasdi, Aikal Liyani (2013)
In recent years, the need for environment protection, due to drastic global climate changes and unprecedented natural disasters, has become a prominent feature in the media. This has created great awareness among people to start preventing the environment from getting further damaged. Consumers are becoming more conscious to purchase products and services which are environmentally friendly which, as a result, lead to the increasing demand for ‘green’ products and services. Companies across all sectors, hospitality sector included, try to make great strides toward instituting green practices and earn green certifications. Restaurants in Malaysia are following this trend and trying to implement green practices. This study investigated consumers’ awareness, perception and attitude towards restaurant green practices and its influence on behaviour intentions. Quantitative approach with descriptive research design was used. Questionnaires were distributed to a convenient sample of 400 shoppers at some well-known hypermarkets and supermarkets in Shah Alam, such as Tesco, Giant, Mydin and SACC Mall. The results show that, consumer awareness, perception and attitude were slightly agreed about restaurant green practices. The findings of this study can help restaurant operators to better understand consumers’ demands and possible behaviour towards green practices.